Comparison of the Risk for Peripheral Vertigo between Physicians and the General Population - Wei-Ta HUANG; Hung-Jung LIN; I-Jung FENG; Chien-Chin HSU; Jhi-Joung WANG; Chien-Cheng HUANG; Shih-Bin SU (Tehran University of Medical Sciences, 2020)
Background: Because of the limited information available regarding peripheral vertigo (PV) in physicians, we conducted this study to clarify this issue. Methods: We used Taiwan National Health Insurance Research Database to identify 26,309 physicians and an identical number of general population matched by age and sex. All the participants who had PV before 2007 and residents were excluded. By tracing their medical histories between 2007 and 2013, comparisons of PV risk between physicians and general population and among physicians were performed. Results: Physicians had a significantly lower PV risk than the general population (adjusted odds ratio [AOR]: 0.811; 95% confidence interval [CI]: 0.662-0.994). In comparison among physicians, otolaryngologists had a significantly higher PV risk than other specialties. Physicians who were older or served in local hospitals or clinics had a significantly higher PV risk than physicians in medical centers. Conclusion: Physicians had a significantly lower PV risk than the general population. Better medical knowledge in physicians than in the general population may explain the findings; however, further studies are warranted for elucidating the detailed mechanisms.